ALGORITHM FOR THE MANAGEMENT OF ENDOTOXIN-INDUCED HEMODYNAMIC DISORDERS - Djamshir K. Uzakov,; Nodir SH. Mirubaydov ,; Nematdjon K. Ibragimov , (Central Asian Journal of Medicine, 2025)
Acute hemodynamic disorders induced by endotoxins pose a serious challenge in emergency medicine, particularly in patients with sepsis and severe inflammatory processes. These conditions are associated with vascular dysfunction, cardiac depression, and impaired organ perfusion, significantly increasing the risk of mortality. This study introduces a novel CDR (Control Damage Resuscitation) Strategy, aimed at a step-by-step assessment and correction of hemodynamic disturbances. The necessity of an individualized therapeutic approach based on dynamic monitoring of hemodynamic parameters is emphasized. Furthermore, modern diagnostic and treatment methods for endotoxemia are discussed, highlighting their potential to enhance the effectiveness of intensive care therapy.